2022
DOI: 10.3389/fendo.2022.839774
|View full text |Cite
|
Sign up to set email alerts
|

Troponin T Is Negatively Associated With 3 Tesla Magnetic Resonance Peripheral Nerve Perfusion in Type 2 Diabetes

Abstract: ObjectiveThe pathogenesis of diabetic polyneuropathy (DN) is poorly understood and given the increasing prevalence of DN, there is a need for clinical or imaging biomarkers that quantify structural and functional nerve damage. While clinical studies have found evidence of an association between elevated levels of troponin T (hsTNT) and N-terminal pro brain natriuretic peptide (proBNP) with microvascular compromise in type 2 diabetes (T2D), their implication in mirroring DN nerve perfusion changes remains uncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, perturbations of those markers were found to gradually increase in severity across HSP, TH and MH and peak in those with SL, thus exhibiting a pattern similar to FA and SNAP. This may indicate that microangiopathic mechanisms may play a primary role in nerve damage and sensory dysfunction in type 2 diabetes, as suggested by previous studies using MRN [ 10 , 12 , 37 , 38 ]. Even though no association between HbA 1c and FA or differences among sensory phenotypes were found in the current study, the positive correlation between HbA 1c and ACR highlights the implication of hyperglycaemia in the pathogenesis of microangiopathy.…”
Section: Discussionmentioning
confidence: 57%
“…Furthermore, perturbations of those markers were found to gradually increase in severity across HSP, TH and MH and peak in those with SL, thus exhibiting a pattern similar to FA and SNAP. This may indicate that microangiopathic mechanisms may play a primary role in nerve damage and sensory dysfunction in type 2 diabetes, as suggested by previous studies using MRN [ 10 , 12 , 37 , 38 ]. Even though no association between HbA 1c and FA or differences among sensory phenotypes were found in the current study, the positive correlation between HbA 1c and ACR highlights the implication of hyperglycaemia in the pathogenesis of microangiopathy.…”
Section: Discussionmentioning
confidence: 57%
“…We found a strong association of hs-troponin T with PN, consistent with our prior work in ARIC 19 and other studies. 37,38 The association of hs-troponin I with PN has not been previously reported to our knowledge. The prevalence of elevated hs-troponin T and hs-troponin I was substantial among adults with both PAD and PN.…”
Section: Discussionmentioning
confidence: 83%
“…Previous studies demonstrated that dynamic contrast enhanced (DCE) magnet resonance imaging (MRI) allows the assessment of peripheral nerve microcirculation [ 17 ]. Recent studies established DCI MRI of the sciatic nerve as a novel imaging biomarker in patients with type 2 diabetes [ 18 20 ]. It was found that a decrease of the sciatic nerve capillary permeability was associated with a decline of electrophysiologic parameters and an increase in clinical neuropathy scores, such as the neuropathy deficit score that allows diagnosis of LFN but not SFN [ 20 ].…”
Section: Introductionmentioning
confidence: 99%